Evaluasi Smart Library Automation (SLA) Menggunakan Framework Human, Organization, and Technology-Fit (HOT-FIT) Model (Studi pada Dinas Perpustakaan dan Kearsipan Kota Batu) - Wreda Beny Ramdhany; Aditya Rachmadi; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Smart Library Automation (SLA) is an information system which is used by the Public Library of Department Library and Archives of Batu City. Information system SLA is used to increase the quality of services to the visitors and facilitate librarians in processing databooks. As an institution which organizes public services by using information technology, libraries must have reliable technology in providing maximum service. In achieving maximum service, an evaluation of Smart Library Automation (SLA) is needed to find out the system's problems in providing services toward the visitors. This study uses a framework Human, Organization, and Technology (Hot-Fit) Model. The main method of collecting data in this study uses qualitative interview methods which are supported by quantitative methods namely questionnaires. It is used to strengthen the results of interviews. The result of this research shows that the quality of the system is good, which is fully supported by the organization in its implementation and this system needs to development in order to fulfill organization's needs in the future in giving excellent library services.